A novel non-sense variant in the OFD1 gene caused Joubert syndrome - Li, Chen; Wang, Xingwang; Li, Fake; Ding, Hongke; Liu, Ling; Xiong, Ying; Yang, Chaoxiang; Zhang, Yan; Wu, Jing; Yin, Aihua (Frontiers in Genetics, 2023)
Background: Joubert syndrome (JBS) is a rare neurodevelopmental disorder associated with progressive renal, liver, and retinal involvement that exhibits heterogeneity in both clinical manifestations and genetic etiology. Therefore, it is difficult to make a definite prenatal diagnosis. Methods: Whole-exome sequencing and Sanger sequencing were performed to screen the causative gene variants in a suspected JBS family. RNA-seq and protein model prediction were performed to clarify the potential pathogenic mechanism. A more comprehensive review of previously reported cases with OFD1 variants is presented and may help to establish a genotype–phenotype. Results: We identified a novel non-sense variant in the OFD1 gene, OFD1 (NM_003611.3): c.2848A>T (p.Lys950Ter). Sanger sequencing confirmed cosegregation among this family. RNA-seq confirmed that partial degradation of mutant transcripts, which was predicted to be caused by the non-sense-mediated mRNA decay (NMD) mechanism, may explain the reduction in the proportion of mutant transcripts. Protein structure prediction of the non-sense variant transcript revealed that this variant may lead to a change in the OFD1 protein structure. Conclusion: The genetic variation spectrum of JBS10 caused by OFD1 was broadened. The novel variants further deepened our insight into the molecular mechanism of the disease.